g Use this to find the equation of the tangent line to the parabola y = 2 x 2 − 7 x + 6 at the point ( 4 , 10 ) . The equation of this tangent line can be written in the form y = m x + b where m is: 9 Correct and where b is: Incorrect LicensePoints possible: 1 Unlimited attempts. Score on last attempt: (0.33, 0.33, 0), Score in gradebook: (0.33, 0.33, 0), Out of: (0.33, 0.33, 0.34) Message instructor about this question

Respuesta :

Answer:

The tangent line to the given curve at the given point is [tex]y=9x-26[/tex].

Step-by-step explanation:

To find the slope of the tangent line we to compute the derivative of [tex]y=2x^2-7x+6[/tex] and then evaluate it for [tex]x=4[/tex].

[tex](y=2x^2-7x+6)'[/tex]          Differentiate the equation.

[tex](y)'=(2x^2-7x+6)'[/tex]       Differentiate both sides.

[tex]y'=(2x^2)'-(7x)'+(6)'[/tex]    Sum/Difference rule applied: [tex](f(x)\pmg(x))'=f'(x)\pm g'(x)[/tex]

[tex]y'=2(x^2)'-7(x)'+(6)'[/tex]  Constant multiple rule applied: [tex](cf)'=c(f)'[/tex]

[tex]y'2(2x)-7(1)+(6)'[/tex]        Applied power rule: [tex](x^n)'=nx^{n-1}[/tex]

[tex]y'=4x-7+0[/tex]               Simplifying and apply constant rule: [tex](c)'=0[/tex]

[tex]y'=4x-7[/tex]                    Simplify.

Evaluate y' for x=4:

[tex]y'=4(4)-7[/tex]

[tex]y'=16-7[/tex]

[tex]y'=9[/tex] is the slope of the tangent line.

Point slope form of a line is:

[tex]y-y_1=m(x-x_1)[/tex]

where [tex]m[/tex] is the slope and [tex](x_1,y_1)[/tex] is a point on the line.

Insert 9 for [tex]m[/tex] and (4,10) for [tex](x_1,y_1)[/tex]:

[tex]y-10=9(x-4)[/tex]

The intended form is [tex]y=mx+b[/tex] which means we are going need to distribute and solve for [tex]y[/tex].

Distribute:

[tex]y-10=9x-36[/tex]

Add 10 on both sides:

[tex]y=9x-26[/tex]

The tangent line to the given curve at the given point is [tex]y=9x-26[/tex].

------------Formal Definition of Derivative----------------

The following limit will give us the derivative of the function [tex]f(x)=2x^2-7x+6[/tex] at [tex]x=4[/tex] (the slope of the tangent line at [tex]x=4[/tex]):

[tex]\lim_{x \rightarrow 4}\frac{f(x)-f(4)}{x-4}[/tex]

[tex]\lim_{x \rightarrow 4}\frac{2x^2-7x+6-10}{x-4}[/tex]  We are given f(4)=10.

[tex]\lim_{x \rightarrow 4}\frac{2x^2-7x-4}{x-4}[/tex]

Let's see if we can factor the top so we can cancel a pair of common factors from top and bottom to get rid of the x-4 on bottom:

[tex]2x^2-7x-4=(x-4)(2x+1)[/tex]

Let's check this with FOIL:

First: [tex]x(2x)=2x^2[/tex]

Outer: [tex]x(1)=x[/tex]

Inner: [tex](-4)(2x)=-8x[/tex]

Last: [tex]-4(1)=-4[/tex]

---------------------------------Add!

[tex]2x^2-7x-4[/tex]

So the numerator and the denominator do contain a common factor.

This means we have this so far in the simplifying of the above limit:

[tex]\lim_{x \rightarrow 4}\frac{2x^2-7x-4}{x-4}[/tex]

[tex]\lim_{x \rightarrow 4}\frac{(x-4)(2x+1)}{x-4}[/tex]

[tex]\lim_{x \rightarrow 4}(2x+1)[/tex]

Now we get to replace x with 4 since we have no division by 0 to worry about:

2(4)+1=8+1=9.